Is the NH4+-induced growth inhibition caused by the NH4+ form of the nitrogen source or by soil acidification? - Wang, Feng; Wang, Qiang; Yu, Qiaogang; Ye, Jing; Gao, Jingwen; Liu, Haitian; Yong, Jean W. H.; Yu, Yijun; Liu, Xiaoxia; Kong, Haimin; He, Xinhua; Ma, Junwei (Frontiers in Plant Science, 2022)
Soil acidification often occurs when the concentration of ammonium (NH4+) in soil rises, such as that observed in farmland. Both soil acidification and excess NH4+ have serious adverse effects on crop growth and food production. However, we still don't know which of these two inhibitors has a greater impact on the growth of crops, and the degree of their inhibitory effect on crop growth have not been accurately evaluated. 31 wheat cultivars originating in various areas of China were planted under 5 mM sole NH4+ (ammonium nitrogen, AN) or nitrate nitrogen (NN) in combined with two pH levels resembling acidified conditions (5.0 and 6.5). The results showed that the shoots and roots biomass were severely reduced by AN in both and these reduction effects were strengthened by a low medium pH. The concentration of free NH4+ and amino acids, the glutamine synthetase activity were significantly higher, but the total soluble sugar content was reduced under NH4+ conditions, and the glutamine synthetase activity was reduced by a low medium pH. Cultivar variance was responsible for the largest proportion of the total variance in plant dry weight, leaf area, nodal root number, total root length and root volume; the nitrogen (N) form explains most of the variation in N and C metabolism; the effects of pH were the greatest for plant height and root average diameter. So, soil acidification and excess NH4+ would cause different degrees of inhibition effects on different plant tissues. The findings are expected to be useful for applying effective strategies for reducing NH4+ stress in the field.